COMBINING PRODUCT AND PROCESS-BASED APPROACHES TO TEACHING WRITING DISCUSSION TEXTS - Vina Agustiana (English Review: Journal of English Education, 2016)
This study examines the activities of teaching-learning writing discussion texts when product and process-based approach combination is implemented in EFL writing classroom, the effects of applying the writing approach on EFL students’ writing skill, and the students’ attitude toward the implementation of writing approach in the classroom. It uses a mixed-methods through applying an embedded design by involving 24 second-grade students of a private university in West Java, Indonesia. There were four instruments used, namely field notes, videotapes, students’ tests (pre-test and post-test), and questionnaires. The findings show that the students were actively involved in class when the teacher applied the writing approach in writing classroom. There was also the improvement in the students’ writing skill based on the result taken from the students’ tests since the level of significance (two-tailed) in paired t-test is less than the alpha (0.0000.05). Qualitatively, the improvements were also found in generic features, textual language, and syntactical language aspects. In addition, the students showed highly positive attitude (4.35 average score) toward the implementation of the approach in the classroom.Keywords: writing, writing skill, discussion texts, product and process-based approach combination